Edible bird's nest effectively attenuates atherosclerosis through modulation of cholesterol metabolism via activation of PPARy/LXRa signaling pathway In Vivo - Mohamad Nasir, Nurul Nadiah; Mohamad Ibrahim, Ramlah; Mahmud, Rozi; Ab Razak, Nor Asma; Ismail, Norsharina; Chan, Kim Wei; Abu Bakar, Md Zuki (Wiley-Blackwell Publishing, 2023)
Atherosclerosis is the underlying cause of the majority of cardiovascular diseases (CVDs) due to high-cholesterol deposition in the aorta, resulting in hardening and narrowing of blood vessels and subsequently leading to an obstructed blood fow. Tere are few previous publications showing the preventive efects of edible birds nest (EBN) on CVD, but the study on cholesterol homeostasis related to atherosclerosis is limited. In this study, we have determined the mechanisms by which EBN modulates cholesterol metabolism by identifying genes and biomarkers. Male New Zealand white rabbits were fed either a high-fat high-cholesterol (HFC) diet or a HFC diet supplemented with EBN (500 mg/kg b.w/day) for 12 weeks. For comparison purposes, a group of rabbits receiving a HFC diet was supplemented with simvastatin (10 mg/kg b.w/day) as a standard drug treatment for hypercholesterolemia. EBN supplementation signifcantly improved lipid and coagulation profles, reduced hepatosteatosis, and stabilized atherosclerotic plaque formation in hypercholesterolemic rabbits. Cholesterol accumulation in liver and aorta tissues, as well as hepatic HMGCR levels, was reduced in the hypercholesterolemic rabbits supplemented with EBN. Gene expression analysis showed that EBN induced many genes related to cholesterol uptake (LDLR, LOX-1, and CD36), cholesterol efux (ABCA1, LCAT, and CYP7A1), and cholesterol-sensing signaling (LXR± and PPARc). In conclusion, our studies suggest that EBN supplementation could be an efective food product for the treatment or prevention of atherosclerosis by regulating cholesterol metabolism.